2010
DOI: 10.1002/mus.21821
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of corticosteroid and mechanical ventilation on diaphragm muscle function

Abstract: Information on the interactive effects of methylprednisolone, controlled mechanical ventilation (CMV), and assisted mechanical ventilation (AMV) on diaphragm function is sparse. Sedated rabbits received 2 days of CMV, AMV, and spontaneous breathing (SB), with either methylprednisolone (MP; 60 mg/kg/day intravenously) or saline. There was also a control group. In vitro diaphragm force, myofibril ultrastructure, αII-spectrin proteins, insulin-like growth factor-1 (IGF-1), and muscle atrophy F-box (MAF-box) mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…IGF1 levels also showed negative correlation with the amount of myofiber injury in the diaphragm, suggesting a protective effect of IGF1 on myofibers during sepsis (26). A second study compared IGF1 expression in the diaphragmatic muscle of rabbits treated with controlled mechanical ventilation (complete diaphragm muscle inactivity) vs. assisted mechanical ventilation (partial maintenance of neural activation and mechanical loading) (27). The authors observed significantly reduced IGF1 mRNA levels with controlled mechanical ventilation, decreasing expression by 65%.…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 levels also showed negative correlation with the amount of myofiber injury in the diaphragm, suggesting a protective effect of IGF1 on myofibers during sepsis (26). A second study compared IGF1 expression in the diaphragmatic muscle of rabbits treated with controlled mechanical ventilation (complete diaphragm muscle inactivity) vs. assisted mechanical ventilation (partial maintenance of neural activation and mechanical loading) (27). The authors observed significantly reduced IGF1 mRNA levels with controlled mechanical ventilation, decreasing expression by 65%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Maes et al (61) reported that, during full support MV, the impact of corticosteroids on VIDD in rats is dose dependent with high doses of corticosteroids (i.e., 30 mg/kg) providing partial protection against VIDD, whereas a lower dose (i.e., 5 mg/kg) exacerbates VIDD. In contrast, Sassoon et al (95) reports that high-dose glucocorticoid administration (i.e., 60 mg/kg) does not protect or exacerbate VIDD in rabbits during full support MV, but this dose of corticosteroids produces deleterious effects to the diaphragm during partial support MV. The reason(s) for the divergent findings in these studies are unclear but could be due to a species difference in the response to corticosteroids.…”
Section: Impact Of Age and Drugs On Mv-induced Diaphragmatic Contractmentioning
confidence: 90%
“…It is worth noting that recent studies suggest that corticosteroid treatment (usually high-dose, short duration) may mitigate the deleterious effects of controlled mechanical ventilation on DIAm structural and functional properties (Maes et al, 2010; Maes et al, 2008; Sassoon et al, 2011). The mechanisms underlying such an effect remain unclear but may include effects on lung injury (and the resultant systemic inflammatory response) or nutritional status in addition to direct effects on the DIAm.…”
Section: Diseases and Conditions Resulting In Selective Diam Fibermentioning
confidence: 99%